A study of tropane derivatives from thorn apple leaves (Datura metel linne) and wild yam tubers (Dioscorea hispida dennst) - Rapepol Bavovada (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 1973